Compulsive Buying Behavior: Clinical Comparison with Other Behavioral Addictions - Granero, Roser; Fernández-Aranda, Fernando; Mestre-Bach, Gemma; Steward, Trevor; Baño, Marta; del Pino-Gutiérrez, Amparo; Moragas, Laura; Mallorquí-Bagué, Núria; Aymamí, Neus; Gómez-Peña, Mónica; Tárrega, Salomé; Menchón, José M.; et al. (Frontiers in Psychology, 2016)
Compulsive buying behavior (CBB) has been recognized as a prevalent mental health disorder, yet its categorization into classification systems remains unsettled. The objective of this study was to assess the sociodemographic and clinic variables related to the CBB phenotype compared to other behavioral addictions. 3,324 treatment-seeking patients were classified in five groups: CBB, sexual addiction, internet gaming addiction, internet addiction, and gambling disorder. CBB was characterized by a higher proportion of women, higher levels of psychopathology, and higher levels in the personality traits of novelty seeking, harm avoidance, reward dependence, persistence, and cooperativeness compared to other behavioral addictions. Results outline the heterogeneity in the clinical profiles of patients diagnosed with different behavioral addiction subtypes and shed new light on the primary mechanisms of CBB.